Evaluation of Prognostic Implication of Serum Mixed Lineage Kinase Domain‐Like Protein in Acute Primary Supratentorial Intracerebral Hemorrhage: A Multicenter Prospective Cohort Study - Yijun Ma; Jun Wang; Chao Tang; Jin Liu; Xiaoyu Wu; Xiaoqiao Dong; Quan Du; Wei Li; Xuan Lv; Suijun Zhu (Brain and Behavior)
Abstract Objective Mixed lineage kinase domain‐like protein (MLKL) is a key component of necroptosis. Here, serum MLKL levels were measured with the intent to assess its prognostic significance in acute intracerebral hemorrhage (ICH). Methods A collective of 161 patients with acute primary supratentorial ICH and 73 controls were enlisted in this multicenter prospective cohort study. Serum MLKL levels were measured at admission in all patients, at study entry in all controls, and on post‐ICH days 1, 3, 5, 7, 10, and 15 in 73 of all patients. Multivariate analyses were adopted to assess relationships between serum MLKL levels, severity, early neurological deterioration (END), poststroke 6‐month modified Rankin Scale (mRS) scores, and poor prognosis (mRS scores of 3–6). Results Patients, relative to controls, had significantly promoted serum MLKL levels from admission until Day 15, with the peaking value at Day 3 (p < 0.001). Admission serum MLKL levels were independently correlated with National Institutes of Health Stroke Scale (NIHSS) scores (beta, 0.133; 95% confidence interval (CI), 0.088–0.178; p = 0.011), hematoma volume (beta, 0.051; 95%CI, 0.037–0.064; p = 0.001), and 6‐month mRS scores (beta, 0.707; 95%CI, 0.487–0.927; p = 0.023), as well as independently predicted END (odds ratio, 1.902; 95%CI, 1.229–2.945; p = 0.014) and poor prognosis (odds ratio, 2.286; 95%CI, 1.324–3.946; p = 0.038). Admission serum MLKL levels were linearly connected to risks of poor prognosis (p > 0.05) and END (p > 0.05), had no interactions with age, gender, hypertension, and so forth (all p > 0.05), and possessed similar areas under the receiver operating characteristic curve to NIHSS scores and hematoma volume (all p > 0.05). The models integrating serum MLKL levels, NIHSS scores, and hematoma volume were graphically represented by nomogram and predicted END and poor prognosis with a good consistency under the calibration curve. Conclusions Serum MLKL levels are markedly increased shortly following ICH, and may accurately mirror disease severity, and efficaciously anticipate END and six‐month bad prognosis of patients, strengthening serum MLKL as a prognostic biomarker of good prospect in ICH.